THE INFLUENCE OF BLOCK CHAIN TECHNOLOGY IMPLEMENTATION OF CONTRACTS IN FIQH MUAMALAH - Samsudin; Asmuni; Tuti Anggraini (RADJA PUBLIKA, 2024)
This paper discusses the use of blockchain technology in the perspective of Islamic economics/Islamic finance. Blockchain technology has changed various sectors, including the financial sector, by providing a secure, decentralized and transparent system. In the context of Islamic economics, blockchain can provide additional benefits by ensuring compliance with sharia principles. This paper outlines how blockchain technology can be used in Islamic finance, such as payment, financing and investment systems that comply with sharia principles. Apart from that, this paper also discusses the potential for using smart contracts in Islamic economics to increase efficiency and transparency in transactions. Through this paper, it is hoped that it can be seen how blockchain technology can strengthen the principles of Islamic finance and facilitate the development of a sharia-based financial sector.